DIRECT AND INDIRECT EFFECT OF GLOBALIZATION ON ECONOMIC GROWTH IN INDONESIA - Qurrota Ayu NINDIEN; Arivina Ratih Yulihar TAHER; Asih MURWIATI; Neli AIDA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2024)
This study examines how path analysis of globalization variables can have a direct effect on economic growth. This study uses the Path Analysis method by reviewing the dynamic modeling between Economic Globalization (GEI), Social Globalization (SGI), Economic Cooperation (KEI), and Economic Growth (GDP) for the period 1970 to 2020 in Indonesia. World Bank and KOFGI ETH Zurich Switzerland publish this data. The results showed that in model (1), there was a direct and significant effect between the KEI variable and GEI of 0.792. Then, in the model (2), the F test or joint test between the GEI, KEI, and SGI variables to GDP has a direct and significant effect. Then, partially, GEI has an immediate and significant impact on GDP, and SGI has a direct and significant effect on GDP. GEI is an intermediary variable for KEI to lead to the path effect to GDP, and this is in accordance with the hypothesis that KEI has an indirect effect on GDP.